STASIUN LRT TAMAN MINI DALAM TRANSISI: DARI TITIK TRANSIT KE PUSAT INTERAKSI DAN EKONOMI - Tiara 'Afifah; Aisyah Zahra Lestari (Saskara : Indonesian Journal of Society Studies, 2026)
This research discusses the transformation of Taman Mini LRT Station from a transit point to a center of social and economic interaction based on Transit Oriented Development (TOD). Through a descriptive qualitative approach, this research explains how the integration of public space and accessibility of transportation modes can shape new meanings. This explanatory research uses a case study approach to space and seeks to explain the cause-and-effect relationship of the phenomena that occur. Data was collected through in-depth interviews, direct observation, and documentation. The results show that transit space can act as a catalyst for social change in the dynamics of urban mobility. This study confirms that modern transit spaces in urban areas are not only places of transit, but also social and economic arenas that reflect the complexity of contemporary urban life.